2008
DOI: 10.4321/s1130-01082008000100010
|View full text |Cite
|
Sign up to set email alerts
|

Estenosis isquémica tardía tras resección anterior de recto

Abstract: INTRODUCCIÓNLa colitis isquémica se complica con el desarrollo de estenosis en el 10-15% de los casos (1). El edema asociado con la isquemia y la fibrosis secundaria al proceso cicatricial se postulan como los mecanismos de dicha estenosis (2).Aunque son relativamente frecuentes las estenosis isquémicas de colon tras cirugía del aneurisma aórtico, existen muy pocos casos descritos tras resección rectal (3), estando casi todos ellos relacionados con radioterapia perioperatoria.Aquí describimos un caso de esteno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…It is reported that after high IMA ligation, tissue oxygen tension is maintained to the distal transverse and descending colon but reduced to the sigmoid colon [ 14 ]. Co-morbidities such as advanced age and atherosclerotic risk factors, particularly smoking, further compromise oxygenation to an anastomosis already reliant on a limited arterial supply [ 1 , 2 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that after high IMA ligation, tissue oxygen tension is maintained to the distal transverse and descending colon but reduced to the sigmoid colon [ 14 ]. Co-morbidities such as advanced age and atherosclerotic risk factors, particularly smoking, further compromise oxygenation to an anastomosis already reliant on a limited arterial supply [ 1 , 2 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…En el lumen gástrico los objetos son frecuentemente retenidos por largos períodos sin presentar consecuencia. 32 Si el objeto no cortante permanece en el estómago puede retrasarse la endoscopía 1-2 meses para darle oportunidad al pasaje espontáneo del objeto 2,33,34 .…”
Section: Discussionunclassified